2014
DOI: 10.1002/sia.5690
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nonmetallic element P in electroless Ni-P coating on the passivation process during chemical conversion treatment

Abstract: Pure Ni and electroless Ni-P coating (ENPC) were passivated by a chemical conversion treatment. The passive films formed on pure Ni and ENPCs (with content of P 2.9, 7.2 and 11.7 at.% respectively) were analyzed by X-ray photoelectron spectroscopy (XPS). High-resolution XPS was also used to analyze the chemical states of the elements detected in the passive films. The results indicated that the detected Ni and P were in elemental states, and no compound with Ni and P element was detected in passive film, meani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In order to enhance the anti-oxidative performance of the ENPC, in the past decades, a chromate conversion treatment using hexavalent chromate as a raw material is widely used because the chromate conversion coating is easy to be obtained and also can improve the anti-corrosive property of the ENPC [19]. Furthermore, in order to alleviate the toxicity of hexavalent chromate, a chromate conversion treatment using trivalent chromate solution as a raw material had also been developed [20].…”
Section: Introductionmentioning
confidence: 99%
“…In order to enhance the anti-oxidative performance of the ENPC, in the past decades, a chromate conversion treatment using hexavalent chromate as a raw material is widely used because the chromate conversion coating is easy to be obtained and also can improve the anti-corrosive property of the ENPC [19]. Furthermore, in order to alleviate the toxicity of hexavalent chromate, a chromate conversion treatment using trivalent chromate solution as a raw material had also been developed [20].…”
Section: Introductionmentioning
confidence: 99%
“…Mu et al concluded that not only Ni but also nonmetallic element P could take part in the passivation reaction. As the content of P increases, Ni–P coating will change from crystalline state to amorphous state, leading Ni and P more difficult to be reacted in passivation solution.…”
Section: Introductionmentioning
confidence: 99%